Day 3 Wed, November 02, 2022 2022
DOI: 10.2118/211011-ms
|View full text |Cite
|
Sign up to set email alerts
|

Case Study on the Application of In-Situ Combustion for Ultra-Low Permeability Oil Shale from Natih B Formation (Oman): Synthetic Oil Generation and Micro-Scale Pore Structure Changes

Abstract: Oil shale is considered as the world's second largest solid fossil fuel resource. Oil shale is an extremely ash-rich sedimentary rock loaded with organic matter. Most of the organic matter is rich in kerogen and a small amount of bitumen, which can be converted into synthetic oil using different thermal treatment methods. In-situ combustion (ISC) is a promising thermal enhanced oil recovery (EOR) method for the conversion of kerogen contained in oil shale to synthetic oil by oxidation. However, its field appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…12,19 Mikhail et al suggested that high-temperature combustion improves reservoir structure, thus optimizing oil flow channels. 20 However, there is currently no research from the perspective of changes in wettability at the oil−water interface during in situ combustion (ISC) to study their contributions to improving recovery. Although Al-Yaseri et al 21 studied the changes in wettability of different rock minerals under calcination processes and further analyzed their effects on recovery rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,19 Mikhail et al suggested that high-temperature combustion improves reservoir structure, thus optimizing oil flow channels. 20 However, there is currently no research from the perspective of changes in wettability at the oil−water interface during in situ combustion (ISC) to study their contributions to improving recovery. Although Al-Yaseri et al 21 studied the changes in wettability of different rock minerals under calcination processes and further analyzed their effects on recovery rates.…”
Section: Introductionmentioning
confidence: 99%
“…The main mechanism of ISC technology is to increase the oil recovery rate by reducing the viscosity of crude oil and enhancing its flowability. , Current research suggests that the in situ upgrading of heavy oil was mainly achieved through complex chemical reactions such as thermal cracking of heavy oil, hydrothermal cracking, , desulfurization, and hydrogenation modification as well as the physical effect of viscosity reduction through CO 2 dissolution . In addition, the generated flue gas, mainly composed of CO 2 and CH 4 , extracts the light compounds from the crude oil, forming a distillation zone together with the thermally volatile hydrocarbon gases, , which was also one of the mechanisms for improving the recovery rate through in situ gas drive. , Mikhail et al suggested that high-temperature combustion improves reservoir structure, thus optimizing oil flow channels . However, there is currently no research from the perspective of changes in wettability at the oil–water interface during in situ combustion (ISC) to study their contributions to improving recovery.…”
Section: Introductionmentioning
confidence: 99%